THE FEAR OF COVID-19 IN THE CONTEXT OFGENDER IN TURKEY - Dağ, Adem; Demirci, Nazlı; Şimşek, Rıdvan; Demirci, Hakan (My University, 2021)
The purpose of this study is to investigate whether the pandemic of\rCoronavirus disease (COVID-19) is experienced differently by men and women in\rterms of gender. The COVID-19 Fear Scale was administered to 265 participants\rusing a web-based data collection method. In order to examine the effects of fear on\rwomen's emotions, 10 participants were given official web-based interview forms.\rQualitative data were analyzed with SPSS 25 Program and t-test. Descriptive analysis\rwas perfomed with the data collected by interview forms and the theme of fear of\rCOVID-19 was examined with 9 codes. A significant difference was found between\rthe COVID-19 fear levels of men and women (p<0.05). As a result of the descriptive\ranalysis, the emotional reflections of fear of COVID-19 in women were found to be\ranxiety, fear, restlessness and harmony/normalization. In terms of gender, women's\rfear of COVID-19 was higher than men. Women who cannot participate in public\renvironments, live dependent on their spouses, and have problems in seeking support\rfor pregnancy and emergencies are more afraid of COVID-19 and reflect this fear on\rtheir emotions.\r
Keywords: Sosyoloji